Improving the nutritive value of palm oil sludge by fermentation : The effect of fungi strain, environmental temperature and enzymatic process - T. Pasaribu; A.P. Sinurat; T. Purwadaria; Supriyati .; J. Rosida; H. Hamid (Indonesian Center for Animal Research and Development (ICARD), 1998)
An experiment was conducted to improve the nutritive value of palm oil sludge (POS) by fermentation process. Aspergillus niger BPT and NRRL 337 were used into fermenting POS for three days and followed by anaerobic enzymatic process. The experiment was arranged in 2x3 factorial design i.e., enzymatic incubation time (2, 3, and 4 days) and environmental temperature during enzymatic process (room temperature and 40°C). Changes on chemical compositions (crude protein, true protein, ADF and NDF), in vitro dry matter digestibility (IVDMD) and protein digestibility (IVPD) were measured. The results showed that both A. niger BPT and NRRL 337 grew well on POS media with the best result at 3 days. The fermentation process by both strains increased crude protein and true protein of POS. The A. niger NRRL reduced the fiber content (ADF and NDF) more than A. niger BPT the IVDMD and IVPD were not significantly affected by fermentation process without enzymatic process. The IVDMD increased significantly when the fermentation followed by enzymatic process. Overall results showed that the best fermentation of POS was obtained by using A. niger NRRL followed by enzymatic process in room temperature for two days. Key words : Palm oil sludge, fermentation, nutritive value